2021
DOI: 10.1038/s41598-021-82967-x
|View full text |Cite
|
Sign up to set email alerts
|

Grading system utilising the total score of Oxford classification for predicting renal prognosis in IgA nephropathy

Abstract: The Oxford classification of IgA nephropathy (IgAN) can evaluate each MEST-C score individually. We analysed a new grading system that utilised the total MEST-C score in predicting renal prognosis. Altogether, 871 IgAN patients were classified into three groups using the new Oxford classification system (O-grade) that utilised the total MEST-C score (O-grade I: 0–1, II: 2–4, and III: 5–7 points), and the 10-year renal prognosis was analysed. The clinical findings became significantly severer with increasing O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…And at the same time, hypertension seemed not to be an independent risk factor to the patients with arteriolar hyalinosis in this study, which is inconsistent with the study of Miyabe et al. [ 36 ]. The possible reasons are that pathological scoring systems for IgAN, such as Oxford classification, without considering arteriolar hyalinosis, and the MESTC primary are also included, while arteriolar hyalinosis is not included in multivariate regression analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…And at the same time, hypertension seemed not to be an independent risk factor to the patients with arteriolar hyalinosis in this study, which is inconsistent with the study of Miyabe et al. [ 36 ]. The possible reasons are that pathological scoring systems for IgAN, such as Oxford classification, without considering arteriolar hyalinosis, and the MESTC primary are also included, while arteriolar hyalinosis is not included in multivariate regression analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, our ROC analysis demonstrated that a model that is based purely on histopathological data has almost the same predictive performance as the models that combine clinical and histopathological information. Recently, Miyabe et al, has demonstrated that the MEST C score could be utilized to predict prognosis in IgAN using a grading system were patients were classified into three groups, but the model has yet to be externally validated [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the widespread use of RASB, its effect on prognosis is underestimated. Some previous studies had not found that RASB has an independent prognostic effect on IgAN [ 39 , 40 ]. The effect of age on the prognosis of IgAN patients remains controversial [ 28 , 33 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%